The fortune men - Mohamed, Nadifa 1981- (Viking, 2021)
"Mahmood Mattan is a fixture in Cardiff's Tiger Bay, 1952, which bustles with Somali and West Indian sailors, Maltese businessmen and Jewish families. He is a father, chancer, some-time petty thief. He is a smooth-talker with an eye for a good game. He is many things, in fact, but he is not a murderer. So, when a shopkeeper is brutally killed and all eyes fall on Mahmood, he isn't too worried. It is true that he has been getting into trouble more often since his Welsh wife Laura left him. But Mahmood is secure in his innocence in a country where, he thinks, justice is served. And at home his three little boys are waiting for him, as is Laura, fierce and full of love, ready to forgive his misbehaviour in a heartbeat if he can just straighten up his act. It is only in the run-up to the trial, as the prospect of freedom dwindles, that it dawns on Mahmood that he is in a terrifying fight for his life - against conspiracy, prejudice and the inhumanity of the state. And, under the shadow of the hangman's noose, he begins to realize that the truth may not be enough to save him." Klappentext
Cover: "Shortlisted The 2021 Booker Prize"
Keywords: Life change events / Fiction; Murder / Investigation / Fiction; Historical fiction; Legal fiction (Literature); Tiger Bay (Cardiff, Wales) / History / 20th century / Fiction; Fiktionale Darstellung